Information searching skills among Malaysian youth: the case of program latihan khidmat negara (plkn) trainees in Selangor - Abd Aziz, Nor Erlissa; Nordin, Siti Arpah; Sahrani, Rosnita (2012)
This paper concerns the area of information searching skills using ICT among Program Latihan Khidmat Negara (PLKN) trainees. Trainees were studied to determine their strengths and weaknesses in terms of their information searching skills. In general, it was found that students had limited skills in the area of searching information. The students were able to plan their searchers but lack the success in executing them because insufficient skills-based training. Based on these findings recommendations were proposed to help develop information searching skills and incorporate their delivery when they enter the higher education.